(untitled) (Proceedings of the International Conference on Future of Women, 2020)
The representation of women has always been different in comics from past to present. Some women have been shown in the comics, in the role of being saved by a male superhero, or in a sexy female image with pornographic elements. The scarcity of female illustrators and writers, being male among publishers consists of the necessary information for the research of comics among the gender studies. Just as there are gender and objectification elements in real life, there are also these approaches to the female body in comics. Towards the 21st century, together with the movements of feminism, both the technological conditions and the digitization of the comics have made women’s representation a little more free. For this reason, the methodology of the research has been determined as Fourth Wave Feminism. Now, they can explain the female lesbian culture and sexual policies independently of society in the comics of Alison Bechdel’s Fun Home and a series of images that depict Belden Sezen’s A Snapshot. The handling of such female characters in comic books and graphic novels firstly enables the students to make accurate determinations while breaking the prejudice of the society, and then when determining the orientation of the young generation, and that women can live their identity freely as an individual. Based on all these information and results, in this research, the representation of women in comics will be explained through a historical evaluation and then criticized in terms of gender.